EFFECT OF PRICE SENSITIVITY ON SUPPLY CHAIN MANAGEMENT IN DELIVERY OF QUALITY SEEDS BY KENYA SEED COMPANY - Chepkoech, Emily; Namusonge, Prof. Gregory (IJRDO - Journal of Business Management, 2016)
Increasingly, the management of multiple relationships across the supply chain is being referred to as supply chain management (SCM). Strictly speaking, the supply chain is not a chain of businesses with one-to-one, business-to-business relationships, but a network of multiple businesses and relationships. The government of Kenya has been pursuing strategies aimed at increasing agricultural productivity as this has been seen to be central to accelerating economic growth and improving the wellbeing of both rural and urban people in Kenya. The aim of the study was to establish the role of effective supply chain management in delivery of quality seeds by Kenya Seed Company. The study specifically focused on price sensitivity affects procurements ability of Kenya Seed Company to deliver quality seeds. The study design was descriptive research and data for the survey were collected using a questionnaire. The study targets management and staff in the procurement department of Kenya Seed Company operating at Kitale branch office.From the population staff a sample of 30% was obtained from the four divisions. The desired sample was obtained using proportionate sampling. After the development of the draft data collection instruments, a pilot study was conducted at National cereals and produce board Kitale to test the questionnaires. Analysis was done using descriptive statistics specifically frequencies and percentages. The study established that production of quality seeds was costly, hence expensive to buy. This was attributed to the fact that seed production is a business venture and therefore profit making is obligatory.